Vaccination Coverage and Its Associated Factors among Children Aged 2 - 5 Years in Eldas Sub County, Wajir County - Abdi, Cathra; Magu, Dennis; Kikuvi, Gideon (Journal of Health, Medicine and Nursing, 2024)
Purpose: The purpose of the study was to determine determinants of vaccination coverage and its associated factors among children 2-5 years of Age in Eldas Sub-County, Wajir County. Methodology: This study used a cross-sectional design with a sample size of 367 participants, selected using probability proportion to size and systematic random sampling. Data was collected using pretested semi-structured questionnaires and a key informants' guide. In the study, Pearson's Chi-square test was used to test the association between complete MR coverage and independent categorical variables. The significance level was fixed at 0.05 (p=0.05) with a 95% confidence interval. Qualitative data was analyzed through content analysis. MS Access database was used to store the data, which was then exported for analysis to SPSS version 21.0. The results were presented in tables, graphs and charts. Findings: The vaccination coverage was 69.8%. The most common reasons for incomplete vaccination coverage were the far location of immunization centers and the unknown place/time of immunization. About 78.5% of the children had experienced illness, while 49.2% of the caregivers had ever taken their child for late immunization. The study found that children whose caregivers did not have personal issues limiting their ability to take their child for immunization were 2.29 times more likely to have complete vaccination coverage (95% CI = 1.41 - 3.75, P < 0.001). Additionally, children whose caregivers had information or education on immunization were 5.53 times more likely to have complete vaccination coverage (95% CI = 3.22 - 9.51, P < 0.001). Other significant predictors of complete vaccination coverage included the importance placed on immunization by the caregiver and the person who facilitated the last delivery. The study concludes that Eldas Sub-County vaccination completeness falls below WHO's recommended target of 85%, with 29.2% partially immunized and 1.1% not immunized. Demographic factors affected completion. Unique Contribution to Theory, Practice and Policy: The study suggested that equipping healthcare providers, providing health education, planning outreach services with community participation, engaging community leaders to address misinformation and designing targeted messages will improve vaccination behavior.